Refining short-range order parameters from the three-dimensional diffuse scattering in single-crystal electron diffraction data - Poppe, Romy; Roth, Nikolaj; Neder, Reinhard B; Palatinus, Lukas; Iversen, Bo Brummerstedt; Hadermann, Joke (IUCrJ, 2024)
Our study compares short-range order parameters refined from the diffuse scattering in single-crystal X-ray and single-crystal electron diffraction data. Nb0.84CoSb was chosen as a reference material. The correlations between neighbouring vacancies and the displacements of Sb and Co atoms were refined from the diffuse scattering using a Monte Carlo refinement in DISCUS. The difference between the Sb and Co displacements refined from the diffuse scattering and the Sb and Co displacements refined from the Bragg reflections in single-crystal X-ray diffraction data is 0.012 (7) Å for the refinement on diffuse scattering in single-crystal X-ray diffraction data and 0.03 (2) Å for the refinement on the diffuse scattering in single-crystal electron diffraction data. As electron diffraction requires much smaller crystals than X-ray diffraction, this opens up the possibility of refining short-range order parameters in many technologically relevant materials for which no crystals large enough for single-crystal X-ray diffraction are available.
Keywords: 3D difference pair distribution functions; 3DED; 3D-ΔPDF; single-crystal diffuse scattering; 3D electron diffraction